Effective Method to Measure and Inspect the Hysteresis Loss of a Transformer - Arunava Chatterjee; Sankar Das; Debashis Chatterjee (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
This paper presents a study on the significance of source side harmonics and their effects on transformers.  Source side harmonics are typically present in power electronic sources which are commonly used in renewable applications. The continued outcome of source side harmonics is observed on the hysteresis curve of a transformer. Single-phase transformers are used in the proposed study to determine the effect of harmonics on magnetization and demagnetization cycles using an electronic operational amplifier-based integrator circuit. A technique is also presented for effectively storing and plotting the hysteresis curve from the measured data. After the hysteresis curve is obtained, it is compared with standard data and a conclusion is obtained from the results about the presence of harmonics in the source. The hysteresis curve is thus found without removing the transformer from operation. The study also proposes a modified hysteresis model for the transformer considering the effect of source harmonics. The proposed study is an effective tool for easy measurement and detection of harmonics. The MATLAB/Simulink based simulations with suitable experiments validate the proposed study.